Implementasi Nilai-Nilai Kesejahteraan Sosial Berdasarkan Al-Qur’an dan Hadits: Studi Kasus di Universitas Islam Zainul Hasan Genggong Probolinggo - Nurul Qomariyah; Ainur Rofiq Sofa (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
This study aims to analyze the implementation of social welfare values contained in the Qur'an and Hadith at Zainul Hasan Islamic University Genggong (UNZAH). Social welfare in Islam encompasses material, moral, and spiritual aspects, emphasizing the importance of social concern and solidarity among individuals. The research method used is a qualitative approach with a case study, where data is collected through interviews, observations, and documentation. The results of the study show that UNZAH has implemented various social welfare programs, such as scholarships for underprivileged and outstanding students, as well as fundraising for the community. Values such as concern, justice, and solidarity are implemented in real activities that involve active participation from the academic community. Although there are challenges such as limited funding and a lack of awareness among some students, supporting factors such as management commitment and a good understanding of Islamic social values provide opportunities for further development. This study recommends expanding the scope of scholarship programs and increasing student involvement in social activities, as well as utilizing technology for fundraising. The findings are expected to serve as a reference for other universities in integrating social welfare values based on Islamic teachings into their policies and campus activities.